2018
DOI: 10.1111/vde.12712
|View full text |Cite
|
Sign up to set email alerts
|

In vitroantimicrobial activity of seven adjuvants against common pathogens associated with canine otitis externa

Abstract: Background -An antibiotic adjuvant is a chemical substance used to modify or augment the effectiveness of primary antimicrobial agents against drug-resistant micro-organisms. Its use provides an alternative approach to address the global issue of antimicrobial resistance and enhance antimicrobial stewardship.Hypothesis/Objectives -To determine the antimicrobial activity of a panel of potential antimicrobial adjuvants against common pathogens associated with canine otitis externa (OE).Animals/Isolates -A number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 45 publications
0
24
0
1
Order By: Relevance
“…Further studies of the antimicrobial adjuvants N‐acetylcysteine (NAC), Tris‐EDTA and disodium EDTA revealed activity against both Gram‐positive and Gram‐negative bacteria (Chan, Khazandi, Hickey, Page, Trott, et al, ). A synergistic effect was seen against P. aeruginosa when narasin was combined with either Tris‐EDTA or disodium EDTA (Chan et al, , submitted). As chronic OE in dogs can be complicated by the presence of biofilms, this study aimed to determine the ability of S. pseudintermedius and P. aeruginosa isolates from cases of canine OE to form biofilm, and to explore the antibiofilm activity of ionophores and adjuvants against these pathogens.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies of the antimicrobial adjuvants N‐acetylcysteine (NAC), Tris‐EDTA and disodium EDTA revealed activity against both Gram‐positive and Gram‐negative bacteria (Chan, Khazandi, Hickey, Page, Trott, et al, ). A synergistic effect was seen against P. aeruginosa when narasin was combined with either Tris‐EDTA or disodium EDTA (Chan et al, , submitted). As chronic OE in dogs can be complicated by the presence of biofilms, this study aimed to determine the ability of S. pseudintermedius and P. aeruginosa isolates from cases of canine OE to form biofilm, and to explore the antibiofilm activity of ionophores and adjuvants against these pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported the in vitro efficacy of repurposed ionophores and antimicrobial adjuvants on pathogens associated with canine OE (Chan et al, 2018a;Chan et al, 2018b;Chan, Khazandi, Hickey, Page, Trott, et al, 2018). The ionophores narasin and monensin, both anticoccidial agents widely used in production animals, were shown to be effective against Gram-positive canine otic pathogens including methicillin-resistant S. pseudintermedius (MRSP), but were not effective against Gram-negative bacteria such as P. aeruginosa (Chan et al, 2018a(Chan et al, , 2018. Further studies of the antimicrobial adjuvants N-acetylcysteine (NAC), Tris-EDTA and disodium EDTA revealed activity against both Gram-positive and Gram-negative bacteria (Chan, Khazandi, Hickey, Page, Trott, et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the technical difficulties of performing multiple checkerboard assays, American Type Culture Collection (ATCC) strains of Staphylococcus aureus (ATCC SA 29213) and Pseudomonas aeruginosa (ATCC PA 27853 and P. aeruginosa biofilm producer ATCC PAO1) were used to assess minimum inhibitory concentrations (MICs). This was considered appropriate because previous studies demonstrated that susceptibility to the test compounds was consistent between the ATCC type strains and a range of clinical isolates from cases of canine OE (n = 110) . This was the case even with meticillin‐susceptible S. pseudintermedius, MRSP and MDRSP.…”
Section: Methodsmentioning
confidence: 96%
“…We showed that Gram‐positive organisms including MRSP and MDRSP from cases of canine OE were highly susceptible to narasin and monensin although these agents lacked activity against Gram‐negative bacteria and had weak anti‐yeast activity . In a study to identify potential adjuvants that might broaden the spectrum of activity of these agents, we reported that N ‐acetylcysteine (NAC), Tris‐EDTA and disodium EDTA had intrinsic antimicrobial activity against otic pathogens, including Gram‐negative organisms …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation